Neuropsychological impairment detected by the Montreal Cognitive Assessment monitors recovery and predicts treatment dropout in substance use disorders - Requena-Ocaña, Nerea; Mañas-Padilla, M. Carmen; Sánchez-Álvarez, Nicolás; Sampedro-Piquero, Patricia; Castilla-Ortega, María Estela (Oxford University Press, 2026)
Background Substance use disorder (SUD) is frequently associated with cognitive impairment that negatively affects treatment adherence and clinical outcomes. Neuropsychological assessments provide detailed information but are often impractical in clinical settings, underscoring the value of brief but sensitive tools such as the Montreal Cognitive Assessment (MoCA). Aims This study aimed to evaluate the utility of MoCA in detecting cognitive impairment in SUD, examining cognitive recovery following sustained abstinence, exploring gender differences in cognitive progression and determining whether baseline cognitive performance predicts treatment dropout. Method Ninety-five SUD patients and 57 healthy controls completed MoCA at baseline and were reassessed after 6 months. Results At baseline, 72.60% of individuals demonstrated cognitive impairment compared with controls, with deficits evident in both global cognition and visuospatial/executive, attention, memory and language domains. Following 6 months of abstinence, deterioration rates decreased to 50%, indicating substantial but not complete recovery, because the improvement in overall cognition was moderate. Male patients showed significantly greater cognitive gains than female patients, particularly in visuospatial/executive and digit span performance. Patients impaired at baseline reported more severe alcohol use and earlier onset of cannabis use disorder. Patients with cocaine use disorder showed the poorest recovery and the highest rate of treatment dropout. Lower baseline language and fluency scores were strongly associated with treatment discontinuation. Language deficits, together with cocaine use disorder, predicted 69% of dropout cases. Conclusions Findings indicate MoCA as a practical screening tool for early detection of cognitive impairment, longitudinal monitoring and personalised treatment planning in SUD.
Keywords: Neuropsicología - Trastornos; MOCA; Cognitive impairment; Substance use disorder; treatment abandonment